Genetic analysis of tolerance to combined drought and heat stress in tropical maize - Melkamu Elmyhun; Ermias Abate; Alemu Abate; Chere, Adefris Teklewold; Menkir, Abebe (2024)
Simultaneous occurrences of heat and drought stresses have a detrimental effect on growth, development and yield of maize. Heat and drought is expected to worsen maize yield losses under climate change. Selecting CDHS tolerant maize hybrids creates great opportunity for sustainable maize improvement in the tropics. The objective of current investigation was to dissect the genetic basis of CDHS tolerance in tropical maize and to determine performance of single cross hybrids under CDHS. Ninety six single-cross hybrids resulted from crossing 12 tassel blast tolerant and 12 tassel blast susceptible lines along with two Striga resistant commercial hybrids, a heat tolerant and a heat susceptible check hybrids were evaluated under FIRR, MDRTS and CDHS using 25x4 alpha lattice design with two replications. The results showed significant genetic variation for FIRR, MDRTS and CDHS tolerance among maize hybrids. The majority of single crosses that showed improved grain yield over their respective standard checks under MDRTS also exhibited improved grain yield over the same checks under CHDS, indicating development of CHDS tolerance hybrids. Significant and positive genotypic and phenotypic correlation of grain yield under MDRTS and CDHS implicated common genetic mechanisms controlling yield under MDRTS and CDHS. Stress tolerance indices YI, GMP, MP, HM and STI were identified as best selecting indices under both stresses. GCA variances were larger than SCA variances in each testing environment for most studied traits indicating the impotence of additive gene action than non-additive gene action to control these traits. Majority of stress indices and SCA effects demonstrated that hybrids HB18, HB41, HB91 and HB95 were high yielder under MDRTS and CDHS. Hybrids HB41, HB91 and HB95 and their parents’ scored minimum tassel blast. Parents 19 and 7 were well general combiner for grain yield and early maturity under MDRTS and CDHS indicting their valuable source of genes for hybridization. The current findings revealed that CDHS tolerance hybrids can reduce expected yield losses and maintain maize productivity in CDHS prone areas. Promising hybrids should be tested further under various drought and CHDS for commercialization.